Relevansi Mitologi Dalam Meningkatkan Keyakinan Umat Beragama - Komang Heriyanti; I Made Hartaka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Mythology became a familiar word to everyone. Some think of mythology as a speech that actually happens and some think of it as just a delusion. But in reality mythology has a very important role if it is associated with religious life. Mythology as an oral or written tradition that is passed down in a particular ethnic group for generations, has been able to provide an image or example for the people supporting the mythology. The values contained in mythology are used as a valuable teaching to increase confidence in God and as a way to foster harmony in life. In ancient times, myths were accepted by primitive peoples or arkais humans, because they were related to nature. The phenomena of nature are manifestations of the holy. The sacred saying (myth) is always a magical secret and beyond human thought. Myth is seen as an attempt by arkais humans to describe the supernatural's trajectory into the world. The existence of myths is largely determined by the supporting community. Although the times are modern, but myths are still believed in modern human life.Keywords: Faith, Mythology, Religious People